The Role of Working Parents in Accompanying Children in Learning English During Online Classes - Melvina Melvina; Marina Lidya (Universitas Negeri Padang, 2023)
Parents have an essential role in the process and results of children's learning. This research was conducted to know the working parents' role in accompanying children to learn English in online classes. This research applied a descriptive qualitative method. The purposive sampling technique was used to select the research subjects. They are two working parents. Data collection used online semi-structured interview techniques using the WhatsApp application. Data reduction techniques, data presentation, and conclusions were used to analyze the data. The results show the role of working parents in accompanying their children to learn English online. Among them are supervising children's learning activities, providing motivation, providing learning facilities, and helping overcome children's learning difficulties.